Live second trimester intrauterine pregnancy with invasive mole: a rare case report - Chhabra, Muskaan; Daver, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Gestational trophoblastic disease or gestational trophoblastic neoplasia is a collective term used to describe hydatiform mole, invasive mole, choriocarcinoma and placental site trophoblastic tumours. Since any molar pregnancy has the potential to develop into invasive mole these patients should be carefully monitored for development of malignant disease. Here we are reporting a case of invasive molar pregnancy with a single live fetus of 17 weeks gestational age. A 24 years old woman, G3P2L2 with a history of amenorrhea since approximately 5 months presented with profuse per vaginal bleeding. Ultrasound showed presence of live fetus of approximate gestational age of 17 weeks. Along with the fetus there was also presence of cystic areas with no vascularity s/o Hydatiform mole. In view of continued bleeding and severe anemia pregnancy was terminated and fetus along with vesicular tissue was expelled. On follow up Beta hcg titers showed increasing trend over the next week. Repeat USG showed extension of molar tissue into the myometrium. In view of this she was given 3 cycles of chemotherapy and eventually was discharged. She was followed up regularly with no e/o recurrence. Presence of viable fetus along with hydatiform mole is a rare occurrence in obstetric practice. After termination of pregnancy these patients should undergo follow up ultrasound and serial beta HCG titers to detect the malignant transformation. Rising beta HCG titers and invasion of myometrium on ultrasound are the ominous features suggesting malignant transformation and should be treated accordingly.